Sustainable good governance, development and democracy - Bhaskara Rao, N. 1940 ,- (SAGE, 2019)
"Despite seven decades of planned development efforts, there remains disparity in distribution of wealth in India. More than half of the national wealth is owned by merely 1 per cent of the population. In 2050, the Indian Republic completes 100 years. A hundred years should be good enough for a country to accomplish its democratic goals as envisaged by its constitution makers. Will India be able to fulfil its objectives in the next 30 years? Sustainable Good Governance, Development and Democracy addresses this question and argues that this is the time for a forthright perspective of what went wrong and how this should be corrected to make headway in the model of governance, development and democracy in India. The book argues that the three pillars of the State--the legislature, judiciary and executive--alone cannot accomplish these goals. It advocates six pillars, including the news media, civil society and political parties, to work in tandem with each other through a 'checks and balances' framework to achieve sustainable good governance"--Publisher's description